Inverse Psoriasis: A Review of Topical Therapies. Issue 1 (December 2016) - Levy, Zachary; Taliercio, Mark; Nia, John K.; Kimmel, Grace; Hashim, Peter W.
Inverse psoriasis, also known as intertriginous or flexural psoriasis, remains a challenging condition to treat. For decades, the mainstay therapy approach has been low-potency steroids for short durations due to the risk of cutaneous atrophy and striae. Other topical options include immunomodulators, vitamin D analogues, and tar-based products. In this paper, we review the literature on the treatment options available for inverse psoriasis.